1975
DOI: 10.1111/j.1751-0813.1975.tb15790.x
|View full text |Cite
|
Sign up to set email alerts
|

ENCEPHALOMYOCARDITIS VIRUS INFECTION OF PIGS 2. Experimental Disease

Abstract: Encephalomycarditis virus recovered from a pig mortality in New South Wales was used to produce experimental infections. Of 34 pigs exposed, 17 died and a further 7 were found to have severe heart lesions when killed. Deaths occurred from 2 to 11 days after exposure with a mode of approximately 3 days. Ten of 11 pigs exposed by intramuscular injection died and the remaining pig was killed after 28 days and found to have severe resolving heart lesions. Of 15 pigs exposed per os to various doses of virus, 6 died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 7 publications
3
29
0
Order By: Relevance
“…Similar findings have also been observed in other experiments with high infectious doses and are common in spontaneous outbreaks of EMCV, when only some animals in the herd fall ill [11,19,21,41]. The starting myocarditis recorded in three pigs at 60-66-hpi implies that the incubation period was longer or that the infection evolved asymptomatically.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar findings have also been observed in other experiments with high infectious doses and are common in spontaneous outbreaks of EMCV, when only some animals in the herd fall ill [11,19,21,41]. The starting myocarditis recorded in three pigs at 60-66-hpi implies that the incubation period was longer or that the infection evolved asymptomatically.…”
Section: Discussionsupporting
confidence: 88%
“…In swine, historical knowledge about the pathogenicity of EMCV indicates the heart as the main target organ [1,2,4,21,22]. In Table I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutralising antibodies can be detected as early as 5 days postinoculation in experimentally infected pigs [1], whereas the virus can be isolated from blood and excreta already one day after inoculation [3,7,17]. EMCV-transmission has been described from rodents to a wide variety of other species, including humans [1,16,22], while a recent study indicated that rats easily spread the virus among each other [24]. Although EMCV-transmission from rodents to pigs is considered important, also the impact of horizontal and vertical pig-to-pig transmission needs to be known/quantified to understand their contribution to the spread of the disease on a pig farm [7,17].…”
Section: Introductionmentioning
confidence: 99%